Efficacy and safety of Isavuconazole for the treatment of invasive Aspergillus infection - an update of the literature - Sivasubramanian, Geetha; Chandrasekar, Pranatharthi H (Expert opinion on pharmacotherapy, 2022)
Invasive aspergillosis is associated with high morbidity and mortality in immunocompromised patients. It is now increasingly reported in critically ill patients, including those with respiratory viral infections, such as influenza and COVID-19. Antifungal management is challenging due to diagnostic delay, adverse drug reactions, drug-drug interactions, narrow therapeutic window, and the emergence of resistance. Isavuconazole is the most recent FDA approved azole for the treatment of invasive aspergillosis, with data continuing to accumulate. The authors review the safety and efficacy of isavuconazole in the management of invasive aspergillosis based on the currently available evidence. The authors also report on the structure, mechanism of action, pharmacokinetic properties, in vitro and in vivo studies as well as clinical safety and efficacy reports of isavuconazole since its FDA approval. Isavuconazole is non-inferior to voriconazole and is a safe, effective, and better tolerated option for the treatment of invasive aspergillosis. It offers several advantages over other antifungal agents, including having a better adverse event profile with respect to hepatotoxicity, neuro-visual toxicity, QTc prolongation, as well as a stable pharmacokinetic profile obviating the need for therapeutic drug monitoring. Further studies are needed to evaluate its performance in prophylaxis against invasive aspergillosis as well as in the treatment of aspergillosis in critically ill patients without underlying cancer or transplant.